1999
DOI: 10.1021/bi990962m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ubiquinol Oxidation by the bc1 Complex:  Different Domains of the Quinol Binding Pocket and Their Role in the Mechanism and Binding of Inhibitors

Abstract: Structures of mitochondrial ubihydroquinone:cytochrome c oxidoreductase (bc 1 complex) from several animal sources have provided a basis for understanding the functional mechanism at the molecular level. Using structures of the chicken complex with and without inhibitors, we analyze the effects of mutation on quinol oxidation at the Q o site of the complex. We suggest a mechanism for the reaction that incorporates two features revealed by the structures, a movement of the iron sulfur protein between two separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
279
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(298 citation statements)
references
References 60 publications
16
279
2
1
Order By: Relevance
“…The histidine ligands take up a proton from the substrate, ubiquinol, upon reduction of the [2Fe-2S] cluster and release it to the intermembrane space when oxidized by cytochrome c 1 , as was suggested recently (31). Glu-295 in cytochrome b is important for the release of the second proton, as proposed previously (31)(32)(33). Glu-295 is completely conserved in mitochondrial cytochrome b (34), and the importance of the residue in proton transfer is indicated by mutagenesis studies because alteration of glutamine abolishes ubiquinol oxidation in R. sphaeroides (35).…”
Section: Photosynthetic Growth Behaviors Of the Wild-type Andsupporting
confidence: 56%
“…The histidine ligands take up a proton from the substrate, ubiquinol, upon reduction of the [2Fe-2S] cluster and release it to the intermembrane space when oxidized by cytochrome c 1 , as was suggested recently (31). Glu-295 in cytochrome b is important for the release of the second proton, as proposed previously (31)(32)(33). Glu-295 is completely conserved in mitochondrial cytochrome b (34), and the importance of the residue in proton transfer is indicated by mutagenesis studies because alteration of glutamine abolishes ubiquinol oxidation in R. sphaeroides (35).…”
Section: Photosynthetic Growth Behaviors Of the Wild-type Andsupporting
confidence: 56%
“…In the native structure the site is vacant. The position of the ISP in our myxothiazole or MOA-stilbenecontaining crystals (23) is the same as in the native structure (7,15,23). A number of features of interest to an understanding of the mechanism of the Q o site should be noted.…”
Section: Positionsmentioning
confidence: 88%
“…We have suggested that the g x ) 1.800 signal reflects the close interaction between quinone bound at the end of the pocket distal from heme b L and the reduced ISP docked at the interface on cytochrome b (15,23). This simple interpretation allows us to use the g x ) 1.800 signal as diagnostic of this interaction and provides a tool to explore the effects of mutation.…”
Section: Mobility and Binding Of The Isp: Complementary Functional Asmentioning
confidence: 93%
See 2 more Smart Citations